1995
DOI: 10.1038/nsb0995-768
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of calcium-free calmodulin

Abstract: The three-dimensional structure of calmodulin in the absence of Ca2+ has been determined by three- and four-dimensional heteronuclear NMR experiments, including ROE, isotope-filtering combined with reverse labelling, and measurement of more than 700 three-bond J-couplings. In analogy with the Ca(2+)-ligated state of this protein, it consists of two small globular domains separated by a flexible linker, with no stable, direct contacts between the two domains. In the absence of Ca2+, the four helices in each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

68
798
2
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 701 publications
(877 citation statements)
references
References 35 publications
68
798
2
2
Order By: Relevance
“…Complementary insights were also obtained from a corresponding analysis of TnC, made by comparing the apo N-terminal domain from the X-ray crystal structure (Satyshur et al, 1994) and the N-terminal domain from the Ca2+-loaded NMR structure (Slupsky & Sykes, 1995). In all cases, the comparisons of the closed and open conformations confirm that Ca2+ binding causes opening within each of the EF-hands, as first predicted by the HMJ model based on the crystal structure of TnC (Herzberg et al, 1986), and subsequently confirmed by NMR solution structures of CaM and TnC (Finn et al, 1995;GagnC et al, 1995;Kuboniwa et al, 1995;Zhang et al, 1995).…”
Section: Caz'-induced Transition From the Closed To Open Conformationmentioning
confidence: 67%
See 2 more Smart Citations
“…Complementary insights were also obtained from a corresponding analysis of TnC, made by comparing the apo N-terminal domain from the X-ray crystal structure (Satyshur et al, 1994) and the N-terminal domain from the Ca2+-loaded NMR structure (Slupsky & Sykes, 1995). In all cases, the comparisons of the closed and open conformations confirm that Ca2+ binding causes opening within each of the EF-hands, as first predicted by the HMJ model based on the crystal structure of TnC (Herzberg et al, 1986), and subsequently confirmed by NMR solution structures of CaM and TnC (Finn et al, 1995;GagnC et al, 1995;Kuboniwa et al, 1995;Zhang et al, 1995).…”
Section: Caz'-induced Transition From the Closed To Open Conformationmentioning
confidence: 67%
“…However, the two proteins have strikingly different conformations in the Ca'+-loaded state. CaM undergoes a large Ca'+-induced conformational change (Finn et al, 1995;Kuboniwa et al, 1995;Zhang et al, 1995). whereas Ca2+ binding has a much smaller effect on the calbindin Dgk structure, and does not lead to exposure of a large hydrophobic surface (Szebenyi & Moffat, 1986;Skelton et al, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each globular domain has two EF-hand structural motifs, which are high affinity binding sites for Ca 2ϩ ions [53][54][55]. Figure 1a shows the mass spectrum obtained from a solution containing apocalmodulin and 18C6.…”
Section: Calmodulinmentioning
confidence: 99%
“…CaM has a dumbbell shaped structure in which two domains, termed the N and C domains, are linked by a flexible helix (Taylor et al, 1991;Finn et al, 1995;Kuboniwa et al, 1995;Zhang et al, 1995). Each domain binds two Ca2+ ions into a pair of EF-hand type sites.…”
mentioning
confidence: 99%